STRUKTUR EPISTEMOLOGI NASKAH TAFSIR SURAT AL-FATIHAH KARYA MUHAMMAD BASIUNI IMRAN SAMBAS, KALIMANTAN BARAT - Parwanto, Wendi (Department of Alquran Science and Interpretation of the Faculty of Ushuluddin, Adab, and Da'wah of IAIN Langsa, 2019)
The research on tafsir of the archipelago usually revolves around familiar tafsir literature, such as Tafsir Tarjuman al-Mustafid by Abd. ar-Ra'uf as-Singkili, Aceh, Tafsir Marah Labid li Kasyfi Ma'ani al-Qur'an al-Majid by Nawawi Al-Bantani, Tanara, Banten, Tafsir Al-Ibriz by Mustafa Bisri, Java and other. And research on tafsir in West Kalimantan has not been done much by researchers. Based on these reasons, researchers are interested in studying this theme further. This study uses a descriptive-analysis method and a historical-philosophical approach. The conclusion of this study is the epistemology of tafsir Surah al-Fatihah by M. Basiuni Imran : 1) the source of intepretation uses al-Qur`an, hadith and ulama?s opinion ; 2) with ijmaliy (global) method, rationality principle based on lexical-linguistic and literal of ayat, and than with textual approach ; and 3) the validation of interpretation contains the truth coherently and pragmaticlly.